The Relationship Between Anxiety and Sleep Quality in Chemotherapy Patients - Ahsan, Zainol; Agustina, Wiwik; Maria, Lilla (Devotion : Journal of Research and Community Service, 2022)
Cancer is the number one cause of death in the world at the end of this century. The impact of the treatment of breast cancer patients on the psychological aspects of experiencing anxiety, and disturbed sleep patterns. The lower the anxiety experienced, the better the quality of sleep, and vice versa. The aim of the study was to analyze the relationship between anxiety levels and patient sleep quality. This research method is cross section with sampling using Accidental Sampling technique. Respondents were 40 breast cancer patients who underwent chemotherapy. The results showed that 82.5% of patients experienced severe anxiety 82.5% and 82.5% had poor sleep quality. The Spearman Rank test results show a correlation value (r) of 0.342 (34.2%) and a p-value of 0.031. P value < (0.05). There is a relationship between anxiety and sleep quality in patients undergoing chemotherapy. It is hoped that it can provide information for health care institutions, which can then be developed for the provision of nursing care in meeting the need for quality sleep for chemotherapy patients.